2013
DOI: 10.1007/s10689-013-9685-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of attitudes regarding preimplantation genetic diagnosis among patients with hereditary cancer syndromes

Abstract: Introduction Preimplantation Genetic Diagnosis (PGD) allows couples to avoid having a child with an inherited condition, potentially reducing cancer burden in families with a hereditary cancer predisposition. This study investigated awareness and acceptance of PGD among patients with hereditary cancer syndromes. Methods Questionnaires were mailed to 984 adults with hereditary breast and ovarian cancer, Lynch syndrome, familial adenomatous polyposis, or multiple endocrine neoplasia type 1 or 2. Associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 35 publications
1
76
0
2
Order By: Relevance
“…In addition to cancer surveillance, carriers of MMR germline mutations can benefit from cancer preventive measures including prophylactic surgeries and preimplantation genetic diagnosis, which will prevent further transmission of the germline mutations to future generations. 13,37,38 Although LS has been extensively characterized in a Western population and the current study is not novel, to the best of our knowledge, the true incidence of LS in Saudi Arabia has not been reported to date. The incidence of LS in all CRC cases in the current study was 0.9%, which is in agreement with incidences reported in earlier studies.…”
Section: Discussionmentioning
confidence: 86%
“…In addition to cancer surveillance, carriers of MMR germline mutations can benefit from cancer preventive measures including prophylactic surgeries and preimplantation genetic diagnosis, which will prevent further transmission of the germline mutations to future generations. 13,37,38 Although LS has been extensively characterized in a Western population and the current study is not novel, to the best of our knowledge, the true incidence of LS in Saudi Arabia has not been reported to date. The incidence of LS in all CRC cases in the current study was 0.9%, which is in agreement with incidences reported in earlier studies.…”
Section: Discussionmentioning
confidence: 86%
“…As the use of this technology has become more accepted and prevalent for BRCA mutations, the attitudes of BRCA mutation carriers have changed. Whereas awareness of PGD for this indication has varied over time from 19%–32% (Menon et al, 2007; Rich et al, 2014), the acceptance of PGD appears to have grown. In 2008, a study reported that only 13% of women whose families were not complete would consider the use of PGD for future pregnancies (Staton et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, a study reported that only 13% of women whose families were not complete would consider the use of PGD for future pregnancies (Staton et al, 2008). A more recent study by Julian-Reynier in 2012 reported that 32.5% of mutation carriers would consider its use for themselves for a theoretical next pregnancy (Julian-Reynier et al, 2012) and a study in 2014 conducted in adults with hereditary cancers found that of 370 respondents, 43% would consider the use of PGD (Rich et al, 2014). What has remained fairly high across time is the percent of BRCA carriers that believe that PGD is acceptable or ethical to offer to carriers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used for more than a dozen hereditary cancer syndromes including HBOC [78]. However, oocyte donation and pre-natal diagnosis in case of BRCA germline mutation are not at all a standard in many countries as ethical questions have been raised about the usage, and also there are other potential factors which include concern about exposure of cancer cells to high estrogen levels during IVF [79] [80]. Alternatively, parents may worry about the possible psychological impact on an existing at-risk child if they choose to have another child who will not be at risk because of PGD.…”
Section: Impact Of Brca Mutation Status For a Woman With Childbearingmentioning
confidence: 99%
“…Alternatively, parents may worry about the possible psychological impact on an existing at-risk child if they choose to have another child who will not be at risk because of PGD. Still, Rich et al [79] suggest that most, but not all, BRCA carriers are interested in hearing about PGD. Therefore, healthcare providers should discuss the availability of reproductive technology with all BRCA carriers in a sensitive manner, acknowledging that some do not condone the procedure.…”
Section: Impact Of Brca Mutation Status For a Woman With Childbearingmentioning
confidence: 99%